Analisis Terhadap Hadist Tentang Larangan Anak Keluar Waktu Malam Hari - Ammar Huzein Nasution; Farid Adnir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe the analysis of the hadith regarding the prohibition of children going out at night. The method used in this research is a descriptive method and uses a qualitative research approach. The techniques used in this research are observation, interviews, documentation with data collection tools, namely observation guides, interviews and field notes. The results of data analysis show that the Tanah Karo community's shared awareness of this prohibition is a form of trust as a point of security in everyday life. This kind of behavior is applied by parents to their children to this day, in order to form individuals who are disciplined and do not spend time just playing. Parents appeal to their children to always limit leaving the house, guide them, such as helping them with evening studies, namely doing homework or just accompanying them. Then, after all the evening activities are finished, this time is used to gather with family or rest. The Prophet required Muslims to look after their children at the beginning of the night by forbidding them from leaving the house, or when they are still babies, carry them and take good care of them because jinns and devils roam around at that time. This command was addressed to none other than the Prophet who was very concerned about the future of children.